Is Being an Elderly Woman a Risk Factor for Worse Outcomes After Percutaneous Coronary Intervention? A Large Cohort Study From One Center. (August 2014) - Gao, Zhan; Yuan, Jin-Qing; Xu, Bo; Yang, Yue-Jin; Chen, Jue; Chen, Ji-Lin; Qiao, Shu-Bin; Wu, Yong-Jian; Yan, Hong-Bin; Gao, Run-Lin
It has remained undefined whether the combination of being elderly (ie, > 75 years old) and female is a risk factor for worse outcomes after percutaneous coronary intervention (PCI). A total of 29 211 consecutive patients who underwent PCI were analyzed. Kaplan-Meier estimated 3-year rate of cardiac death was significantly higher in elderly females in comparison with all other groups ( P < .05). Using Cox proportional hazard models, being an elderly female was a significant risk factor for cardiac death and cardiac death/MI in comparison with being a young female, OR (95% CI): 2.53 (1.15-5.59), 2.26 (1.27-4.03), or young male, OR (95% CI): 2.22 (1.26-3.91), 2.25 (1.44-3.51); however, it was not a significant risk factor in comparison with being elderly male, OR (95% CI): 1.30 (0.97-1.71), 1.21(0.94-1.55). Elderly females had worse outcomes after PCI therapy than other gender and age groups, but being an elderly female was not an independent risk factor for worse PCI outcomes.